Program of expressive practical through the art in an elementary school (Palíndromo, 2015)
In our society, which has many social issues, the school can play an important role in the human formation by offering some teaching that can emphasize the de- velopment of sensitivity, integrating several fields of knowledge and encouraging social and emotional competences. According to texts of National Curriculum Analyses, edu- cation must be committed to citizenship, which means to consider social and envi- ronmental views as the subject of reflection. For this purpose education should be seen interconnected with the areas of human development responsible for triggering the sensitivity and the emotion: art and aesthe- tics. It is understood that the combination of education and art can help build up a better human society. This study analyzed a pro- gram of meaningful activities through Art in an elementary school with the objective of contributing to the human formation.
Keywords: education; appearence education; art; sensitivity; emotion